200 keV electron beam pulse source for the complex VEPP-5 preinjector - Akimov, V.E.; Kazarezov, I.V.; Korepanov, A.A.; Frolov, A.R.; Tsyganov, A.V. (Вопросы атомной науки и техники, 2001)
The electron beam source based on GS-34 valve cathode-grid unit with oxide cathode of 12 mm in diameter is described. Originally the high voltage DC source was used to supply the gun. The cathode emission characteristic was reduced by the vacuum breakdowns during gun operation. So the necessity of decreasing a high voltage from 200 kV to 140 kV has appeared. The use of the pulse transformer based gun supply with a pulse duration of ~1 mcs provided the gun operation without breakdowns at a voltage of 200 kV and pulse repetition rate up to 50 Hz. At present time the electron source is operated at the complex VEPP-5 preinjector.